Nursing Advocacy in Procedural Pain Care - Vaartio, Heli (Nursing ethics, 2009)
In nursing, the concept of advocacy is often understood in terms of reactive or proactive action aimed at protecting patients' legal or moral rights. However, advocacy activities have not often been researched in the context of everyday clinical nursing practice, at least from patients' point of view. This study investigated the implementation of nursing advocacy in the context of procedural pain care from the perspectives of both patients and nurses. The cross-sectional study was conducted on a cluster sample of surgical otolaryngology patients (n = 405) and nurses (n = 118) from 12 hospital units in Finland. The data were obtained using an instrument specially designed for this purpose, and analysed statistically by descriptive and non-parametric methods. According to the results, patients and nurses have slightly different views about which dimensions of advocacy are implemented in procedural pain care. It seems that advocacy acts are chosen and implemented rather haphazardly, depending partly on how active patients are in expressing their wishes and interests and partly on nurses' empowerment.